Seasonal sea-surface carbon dioxide in the Azores area - Ríos, Aida F.; Pérez, Fiz F.; Álvarez-Rodríguez, Marta; Mintrop, Ludger; González-Dávila, Melchor; Santana-Casiano, Juana Magdalena; Lefèvre, Nathalie; Watson, Andrew J. (Marine Chemistry, 2005)
17 páginas, 8 figuras, 2 tablas The seasonal evolution of total inorganic carbon and CO2 air–sea fluxes in the Eastern North Atlantic Subtropical Gyre (Azores area) was investigated by means of studying a data set from 10 cruises covering a seasonal cycle. Monthly CO2 fugacity was modelled as a function of surface temperature and month for 1998. So, the seasonal cycle of CO2 and its air–sea fluxes were obtained using monthly average surface data in the area. Over the year, the Azores area (2.25d 1012 m2) acts as a weak net sink of CO2 (0.38 mmol m 2 day 1). From December to May, the zone is a rather strong sink for CO2 (10.3 mmol m 2 day 1), while between June and November, it behaves as a CO2 source (9.9 mmol m 2 day 1), August presents the highest outgassing (3.88 mmol m 2 day 1). Moreover, a box budget was established to evaluate the relative contribution of the physical and biological processes affecting the seasonal CO2 variability in the mixed layer of the Azores area. The most important contributor to the average mass balance of CO2 was the mixing with the lower layer (7.8 mmol m 2 day 1) and biological activity ( 8.9 mmol m 2 day 1). Conversely, air–sea exchange (0.17 mmol m 2 day 1) and advection (1.7 mmol m 2 day 1) contribute with a very small input. There is a strong coupling between biological activity, advection, and mixing in the mixed layer depth. The biological activity is supported by mixing and advection that provide CO2 and nutrients to the mixed layer, so we combine the three processes in only one term (DCAMB) that represents the net biology production in the water column, and re-evaluated the CO2 mass balance to discriminate the importance of the physical and biological contributions. The effect of temperature, wind, and net biological process contribute in 42%, 12%, and 46%, respectively, to the explained variance of total CO2 mass balance in the upper layer. This work was supported by the EU CAVASSOO project (EVK2-2000-00088) and EU CANIGO project (MAS3-CT96-0060). M. A´ lvarez was ...